Secagem convectiva de finos de minério de ferro: aplicação de um ciclone separador como equipamento de secagem - Genaro, Luana Boger (2025)
Iron ore is the primary raw material for steel production. In Brazil, once extracted from the mines, the ore is transported by rail to ports, where it is loaded onto ships for export. Throughout these stages, the high moisture content of the material can cause operational challenges, such as pipeline blockages, conveyor belt misalignment, and difficulties in the pelletizing process. Moreover, if the ore’s moisture content exceeds the Transportable Moisture Limit (TML), the cargo may be rejected, preventing its shipment. Currently, iron ore drying technologies are being researched, focusing on the implementation of convective dryers for this purpose. However, due to the injection of hot air at high flow rates and the particle size distribution of the ore, the top stream of these devices may carry away particulate material with residual moisture. In this context, the objective of this study is to evaluate the potential of using a cyclone separator as a dryer for mining products through bench-scale testing and computational simulation. To theoretically estimate the feeding conditions of an industrial cyclone, mathematical modeling and simulation of the iron ore drying process in the pneumatic conveyor connecting the convective dryer to a cyclone battery, were performed. In the bench-scale cyclone drying experiments, the influences of air velocity and temperature, feed moisture content, and solid feed rate on the moisture content of the ore collected at the cyclone underflow were evaluated. Additionally, using the Eulerian Granular model, a Computational Fluid Dynamics (CFD) simulation of the continuous drying process in the cyclone was conducted. To determine mass transfer coefficients, fixed-bed drying experiments and thin-layer mathematical modeling were performed. In the fixed-bed and thin-layer drying experiments, the diffusive models showed good agreement for temperatures of 60, 70, and 80 °C. The effective mass diffusivity values obtained ranged between 1.75·10-9 m²·s-1 and 8.25·10-9 m²·s-1 for the convective diffusive model. In the thick-layer fixed-bed drying experiments, moisture and temperature gradients were observed at different axial positions of the bed. The theoretical estimates from the pneumatic conveyor drying simulation indicated that particles with diameters greater than 50 µm, which are carried by the air, tend to retain residual moisture when reaching the cyclone battery. In the cyclone drying experiments, the smallest reduction in the moisture content of the ore collected at the underflow was 70 %, achieved at a drying temperature of 80 °C, a solid feed moisture content of 0.10 kgwater·kgwet solid−1, and a solid feed rate of 18.3 gwet solid ·s−1. For the other drying conditions, the moisture content of the ore collected at the underflow was close to zero. These results highlight the high potential of using a cyclone separator as an iron ore dryer. The CFD simulation results aligned with the physical and experimental expectations for the iron ore drying process in the cyclone.